Pengaruh Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan (Studi Kasus PT. Pegadaian Kantor Wilayah IX Jakarta 2 Tahun 2024) - Annaassya, Adinda Arzeti; Taufiqurahman, Endang (Peneliti.net, 2025)
Employee Performance of PT employees. Pegadaian Regional Office IX Jakarta 2 can be influenced by many factors, including Job Satisfaction and Work Motivation. This research aims to test, analyze and describe the influence of Job Satisfaction and Work Motivation on PT Employee Performance. Pegadaian Regional Office IX Jakarta 2. This research was conducted using descriptive and verification quantitative methods, namely to find out, analyze and describe hypothesis testing and make conclusions and suggestions. Sample determination was carried out using a saturated sampling technique, namely, using the entire population with a total of 58 respondents. The data analysis techniques used are scale range analysis techniques and multiple linear regression analysis using SPSS 24. The results of the research show that Job Satisfaction and Work Motivation on PT Employee Performance. Pegadaian Regional Office IX Jakarta 2. Partially, there is a significant influence between Job Satisfaction (X1) on Employee Performance of 24.9% and there is a significant influence between Work Motivation (X2) on Employee Performance (Y) of 30.8%. Furthermore, simultaneously there is a significant influence between Job Satisfaction and Work Motivation on Employee Performance of. Meanwhile, the remaining 79.1% is influenced by other variables not examined in this research. Based on the Coefficient of Determination (R2) value, the Adjusted R square value is only 0.209 or 20.9%. This shows that only 20.9% of the job satisfaction and work motivation variables have a significant influence on the performance of PT. Pegadaian Regional Office IX Jakarta 2 employees. Meanwhile, the remaining 79.1% is influenced by other factors that were not examined in the research This.